2023
DOI: 10.1093/mnras/stad2782
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic classification of infrared-selected targets for SPHEREx mission: in search of young stellar objects

K Lakshmipathaiah,
S Vig,
Matthew L N Ashby
et al.

Abstract: We apply machine learning algorithms to classify infrared (IR)-selected targets for NASA’s upcoming Spectro-Photometer for the History of the Universe, Epoch of Reionization and Ices Explorer (SPHEREx) mission. In particular, we are interested in classifying young stellar objects (YSOs), which are essential for understanding the star formation process. Our approach differs from previous works, which have relied heavily on broad-band colour criteria to classify IR-bright objects, and are typically implemented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
0
0
Order By: Relevance
“…Wilson et al (2023) identified 6504 Class II YSOs (threshold posterior greater than 0.5) in Gaia EDR3 using a naive Bayesian classifier. Lakshmipathaiah et al (2023) applied a machine learning algorithm to classify infrared selected targets for NASA's SPHEREx mission, resulting in 34,062 YSO candidates. Vioque et al (2020) developed an ANN method to search for new Herbig Ae/Be and pre-main-sequence (PMS) stars, yielding a catalog of 8470 new PMS candidates and 693 new classical Be stars.…”
Section: Introductionmentioning
confidence: 99%
“…Wilson et al (2023) identified 6504 Class II YSOs (threshold posterior greater than 0.5) in Gaia EDR3 using a naive Bayesian classifier. Lakshmipathaiah et al (2023) applied a machine learning algorithm to classify infrared selected targets for NASA's SPHEREx mission, resulting in 34,062 YSO candidates. Vioque et al (2020) developed an ANN method to search for new Herbig Ae/Be and pre-main-sequence (PMS) stars, yielding a catalog of 8470 new PMS candidates and 693 new classical Be stars.…”
Section: Introductionmentioning
confidence: 99%